HUMAN LANGUAGE ACQUISITION AL-QURÁN PERSPECTIVE - Dariyanto; Nabil (Almarhalah: Jurnal Pendidikan Islam, 2023)
The study of human language and how humans acquire language is the interesting subject to linguistic experts. The Koran, with Arabic as a religious language, explicitly and implicitly provides globally and comprehensively signals about how humans acquire language. This research aims to: 1) explain the meaning of language and the features of human language from linguists. 2) explain how humans acquire the language perspective of the Koran. Using the literature method, the interpretations of Al-Quran exegetes provide an explanation of how humans acquired their language. Human language has more features and uniquies. In the Al-Qurán, it is explicitly and implicitly explained that language teaching starts to recognize the names of objects, which is the most important part of how humans acquire language through the process. Fundamentally, to introduce formally or informally teaching the names of objects and their functions is an important basis to master a language.